Academic Senate Minutes 2008-04-10 - Academic Senate:::::::::
Chair Report. Agenda approved. Minutes of 3/6/08 approved. Revision to M.A. in Organizational Development approved. Update on WASC. Associated Students Report. Resolution re: Staffing Ratios in Student Counseling and Psychological Services – First Reading. Academic Calendar Guidelines – First Reading. Resolutions on Blood Banks and Non-Discrimination – First Reading. Course Outline Policy revision – First Reading. RTP revision – Second Reading. Ad-Hoc Committee Business – Diversity Resolution – First Reading.